Analisis Perbandingan Kinerja Keuangan Bank Syariah Devisa Dengan Bank Syariah Non Devisa Periode 2012-2014 - Yuli Muhayati; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This study aims to compare and see the differences between foreign Islamic bank and non-foreign Islamic bank by using method RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital). This study examines the comparison in financial performance of four foreign Islamic banks and 6 non-foreign Islamic banks. The collection of data in this study was done by collecting all the annual reports of banks that has been created as a sample over the period 2012-2014.The test result of the Independent Samples T-test showed there was no differences in the financial performance of foreign Islamic banks exchange with Non-foreign Islamic Bank exchange as seen from the aspect of Risk profile (NPF and FDR), GCG, Earnings (ROA), and (CAR). While there are differences of financial performance as seen fromEarnings (NOM) aspect.